Relationships between avian exposure, humoral immune response, and pigeon breeders' disease among Scottish pigeon fanciers. - Banham, S W (1986)
In a large scale clinical survey of Scottish pigeon fanciers, 277 people completed a detailed questionnaire and provided a venous blood sample. There were 29 (10.4%) who fulfilled the clinical criteria for pigeon breeders' disease used in the study and 84 (30.3%) who showed a significant serum IgG antibody response to pigeon gammaglobulin (4 micrograms/ml) and were considered to have been sensitised. Increasing exposure was associated with a progressive tendency towards sensitisation, but the intensity of the antibody response was related to the presence of symptoms and not the degree of exposure. Thirteen out of 15 subjects in the survey with a serum concentration of antipigeon IgG greater than 60 micrograms/ml fulfilled the clinical criteria for pigeon breeders' disease, and those affected within 10 years of starting the hobby had the highest mean antibody response. Accurate quantitation of antibody response is therefore helpful in the investigation of pigeon breeders' disease. The radioimmunoassay provides a quantitative method for determining antibody response that can be used in the routine screening of pigeon fanciers and in serial monitoring of their response.